THE IMPACT OF MODERN TECHNOLOGIES AND DIGITAL MARKETING ON TOURISM - Dalaboyeva Shodiya (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article examines the transformative role of modern technologies and digital marketing in the tourism industry. It explores how digital tools such as artificial  intelligence,  big  data,  virtual  reality, and  social  media  marketing  enhance tourist experiences, streamline operations, and boost destination competitiveness. The study  highlights  key  trends,  challenges,  and  future  prospects  of  technology-driven tourism.